2013
DOI: 10.1103/physreve.88.033103
|View full text |Cite
|
Sign up to set email alerts
|

Negative plasma potential relative to electron-emitting surfaces

Abstract: Most works on plasma-wall interaction predict that with strong electron emission, a nonmonotonic "space-charge-limited" (SCL) sheath forms where the plasma potential is positive relative to the wall. We show that a fundamentally different sheath structure is possible where the potential monotonically increases toward a positively charged wall that is shielded by a single layer of negative charge. No ion-accelerating presheath exists in the plasma and the ion wall flux is zero. An analytical solution of the "in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 34 publications
3
67
0
1
Order By: Relevance
“…In this study, only the classic sheath and critical SCL sheath, 6,[18][19][20][21][22][23][24][25][26] i.e. φ monotonically decreases along x direction, is considered.…”
Section: A Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, only the classic sheath and critical SCL sheath, 6,[18][19][20][21][22][23][24][25][26] i.e. φ monotonically decreases along x direction, is considered.…”
Section: A Theoretical Modelmentioning
confidence: 99%
“…6 They found that sheath potential drop decreases with increment of Γ, and thereby heat flux at wall increases; when Γ reaches a critical value Γ c,SCL = 1 8.3(m e /m i ) 0.5 , the sheath goes into space-charge limited (SCL) regime, with wall potential relative to sheath edge φ w = 1.02T e /e and wall electric field equals zero, where m e and m i are the masses of electron and ion respectively, T e is plasma electron temperature and e is the unit charge. Some other kinetic sheath models combined with PIC or Vlasov kinetic simulation also found that strong electron emission causes sheath structure transition from classic sheath to SCL sheath; [20][21][22][23][24] while the sheath was predicted to transit to an inverse Debye layer structure with a fixed ion flux through the sheath region, 25 and a more entirely inverse sheath structure with no ion through the sheath region; 26 and if ion collisions are included, these collisions cause ions get trapped in virtual cathode and force a transition to the inverse sheath. 27 The effect of emitted electron temperature (EET) on potential of critical SCL sheath was specially investigated in recent several years by Sheehan et.al with kinetic theory analysis, particle-in-cell simulation and experiment measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theory [10] and simulation [11,12,13] studies have demonstrated a second solution type. In the "inverse regime" the sheath potential is positive, opposite in sign from the SCL.…”
mentioning
confidence: 99%
“…1 (see Ref. [10] for further discussion). For γ > 1, the SCL and inverse models both give valid solutions with the required emission barrier.…”
mentioning
confidence: 99%